Study of the Achievement of University Students and Their Relationship with the Selection Process - Palominos-Villavicencio, F; Diaz-Munoz, H (Elsevier B.V., 2017)
This paper explores the performance of students from four university careers of scientific orientation, per the qualifications and the effective progress achieved in their corresponding curricula, as well as their relationship with the variables of the admission process and the subsequent performance. Under the assumption that grades are less representative than the progress achieved by the student, the returns are measured mainly in terms of the progress achieved by the student in his / her respective curriculum. The analysis was approached by means of the application of the test of equality of average and the coefficient of correlation of Pearson, in subgroups of students formed per their condition of novices or previous experience in the university, its career and its type of school of origin. The results show little connection between the variables of the selection process and the academic performance, as well as a poor relationship between the indicators related to the secondary education grades and the performance of the students in their respective careers. Finally, a particular conceptual approach for the solution based on neuro-management considerations as a model to conceptually aboard complex dynamic routines that need to be redirected. © 2017 The Authors. Published by Elsevier B.V.